2000
DOI: 10.1001/jama.283.23.3089
|View full text |Cite
|
Sign up to set email alerts
|

Invasive <EMPH TYPE="ITAL">Haemophilus influenzae</EMPH> Disease in Alaskan Residents Aged 10 Years and Older Before and After Infant Vaccination Programs

Abstract: The overall statewide incidence of invasive H influenzae infections in unimmunized persons aged 10 years and older decreased after the initiation of an infant Hib vaccine program, perhaps by decreasing Hib carriage in child reservoirs. An increase in non-serotype b strains was observed. This trend justifies the need for continued surveillance of invasive disease caused by H influenzae. JAMA. 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 31 publications
5
59
0
4
Order By: Relevance
“…Clinical manifestations of invasive Hia disease were similar to those of invasive Hib disease in the prevaccine era (29). Meningitis was more common among Hia infections than in infections caused by encapsulated non-a and non-typeable Hi infections (37% vs. 24% and 12%, respectively, p = 0.05); conversely, pneumonia was less common (32% Hia vs. 41% encapsulated non-a H. infl uenzae and 40% nontypeable H. infl uenzae); however, this fi nding was…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Clinical manifestations of invasive Hia disease were similar to those of invasive Hib disease in the prevaccine era (29). Meningitis was more common among Hia infections than in infections caused by encapsulated non-a and non-typeable Hi infections (37% vs. 24% and 12%, respectively, p = 0.05); conversely, pneumonia was less common (32% Hia vs. 41% encapsulated non-a H. infl uenzae and 40% nontypeable H. infl uenzae); however, this fi nding was…”
Section: Discussionmentioning
confidence: 59%
“…However, the potential for serotype replacement remains a concern (16). Three population-based studies have documented small increases in the incidence of non-type b H. infl uenzae disease after the introduction of the Hib conjugate vaccine (28)(29)(30). Several recent studies conducted in different countries have demonstrated a predominance of serotype a disease.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of serious infection caused by non-type b encapsulated H. influenzae is currently much lower than that of Hib infections in the prevaccine era; however, for several reasons, public health experts recommend continued surveillance of invasive disease caused by these bacteria (21). First, invasive infections due to non-type b encapsulated H. influenzae have increased in relative importance with the decline of Hib disease (7,18,21).…”
mentioning
confidence: 99%
“…2,12 A study of Native Alaskans reported Hib oropharyngeal carriage as high as 9.3% in fully vaccinated under five year old children. 54 Other studies in Alaska found carriage rates up to 13.2% in a 97% vaccinated population, with authors concluding that carriage is the driving force behind Hib disease resurgence in remote Alaska. 53 More recently health researchers have reported resurgence of Hib carriage UK, in fully vaccinated school children.…”
Section: Risks Associated With Hib Carriagementioning
confidence: 97%